Membangun Konsep Niat Berkunjung Kembali Ke Desa Wisata Di Kabupaten Buleleng Bali - Komang Ary Pratiwi; I Made Sudarsana; I Putu Mahendra Adi Wardana (Jurnal Ekonomi, 2024)
Bali is part of Indonesia whose economy is dominated by the tourism sector, and tourist villages have become an alternative tourism which is a current trend and helps the recovery of the Balinese economy after the Covid pandemic. The aim of this research is to determine and explain the variables that influence the concept of intention to return to a tourist village, such as servicescape, destination image, customer satisfaction and local wisdom of Tri_Kaya_Parisudha. The research methodology used is descriptive statistical analysis and inferential statistical analysis, namely using SEM PLS. The sample for this research consisted of 190 respondents, using a sampling technique, namely purposive sampling. Thus, the results of this research findings are 8 hypotheses that are accepted and have a significant effect.